Methodological Reflections of the Concept of Discourse in Sociological-Historical Research of Academic Discipline - Kraniauskas, Liutauras (Problemos, 2002)
The article discusses sociological potential of the concept of discourse in sociological-historical research of academic disciplines. In SSK scientific knowledge is understood as an output of complex social process as any other kind of social knowledge. In sociological perspective, the concept of discourse is not used as a synonym of a text. In the sociological discourse analysis, attention is shifted from analysis of inner structure of a text and hidden meanings to social context of text production. Methodological principles of M. Foucault's archeology of knowledge emphasize social practices of discourse production; analysis of scientific discourses (N. Gilbert and M. Mulkay) examines contextual meanings of interpretations concerning social actions of scientists; Bourdieu's research of academic field explores the process of intellectual and social legitimation of scientific knowledge. Sociological concept of discourse connects a class of texts to social conditions of its production. Social context determines the status of a text and its inclusion into the text class of an academic discipline. In this perspective, every academic discipline is understood as an object for sociological analysis. The scope of sociological discourse analysis covers institutional development of academic organizational structures, transformations of a category of the discipline in a general taxonomy system of academic disciplines, changes of other social circumstances structuring patterns of knowledge production and composition of texts.